Peran Mahasiswa dalam Mendorong Pengelolaan Sampah Menuju Pembangunan Desa Berkelanjutan - Putri Ayu Amalia Firdaus; Khofifatul Hasanah; M. Nur Cholis; Devina Ayu Trisna; Luluk Purnamasari; Firmansyah Jamal; Tanti Ayu Safrida; Amanda Chorunnisa’; Najwa Nabiha; Angelika Angelika; Nahda Diva; Mariatul Kiptiah; Binti Nafisatul Muthoharoh; M. Nur Manan Alfatah; Maghfirotun Nikmah; Mokhammad Miftakhul Huda (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
The waste problem in Tamanan village is an issue that needs serious attention because of its impact on environmental pollution and public health. One of the main challenges is the low awareness of residents, especially elementary school children, in terms of good and correct waste management. A lot of waste is thrown carelessly without sorting, which results in a decrease in the quality of cleanliness and health of the village environment. This community service program aims to improve students' understanding and skills in waste management through a Participatory Action Research (PAR) approach for 40 days. This program involves students of MI Nurur Rahman and SDN Tamanan 1 as the main subjects. The activities carried out include socialization about the importance of waste management, the delivery of material on types of waste, as well as the practice of sorting organic, inorganic, and B3 waste. In addition, the installation of educational media in the school environment and evaluation monitoring were also carried out. The results of the evaluation showed that 73% of students were able to answer the quiz questions correctly ≥70%, which indicates their good understanding of waste management. Some students also began to implement the habit of separating waste at home and inviting families to participate. Support from village officials and the existence of educational media are expected to strengthen the sustainability of this program. Participatory approaches have proven to be effective in raising environmental awareness and can be implemented sustainably through collaboration between schools, communities, and village governments.